First record of the family Ameronothridae (Acari: Oribatida) from Japan – new species, juvenile morphology, ecology and biogeographic remarks. Issue 5 (4th July 2019) - Pfingstl, Tobias; Hiruta, Shimpei F.; Wagner, Maximilian; Hagino, Wataru; Shimano, Satoshi
ABSTRACT: The Ameronothridae are recorded for the first time from Japanese coasts with the new species Ameronothrus yoichi sp. n. from Hokkaido. The report of this species represents the most southern occurrence of an Ameronothrus species in the Asian Pacific region. Ameronothrus yoichi sp. n. can be easily distinguished from its congeners by the conspicuously pusticulate body surface and the loss of dorsal companion setae d on all genua in the adult stage. Based on adult and juvenile morphology, a close relation to Ameronothrus maculatus and A. schneideri is suggested. Ameronothrus yoichi sp. n. is classified as a lichenivorous inhabitant of sediment-free rocky coastal substrates. Due to a lack of genetic sequence data of nearly all ameronothrid species a molecular genetic comparison is yet unfeasible, but a Bayesian inference tree based on the 18S rRNA gene shows a paraphyletic clustering of the ameronothrid A. yoichi sp. n. and Paraquanothrus grahami . http://www.zoobank.org/urn:lsid:zoobank.org:pub:5B772E2C-7D5E-4C86-9955-AB84A84C50DA Graphical abstract: